Pengaruh Kualitas Produk Dan Harga Terhadap Minat Beli Konsumen Smartphone Bergaransi Distributor Pada PT. Tiga Agung - Adrian Hidayat; Gustin Hartanto (Komunitas Dosen Indonesia, 2019)
The Influence Of The Quality Of Products And Prices On Interest In Buying Smartphone Consumers Warranty Of Distributors In Pt. Tiga Agung Abstract As the technology age grew also became more sophisticated. As well as a communication tool that we know is a smartphone, where this smartphone can make it easier for users to do things easier. So many companies are making smartphones because the demand market for a smartphone is greatly improved. The purpose of writing this thesis is to know the extent to which the influence of product quality and price to consumer buying interest Smartphone warranty distributor at PT. Tiga Agung (Case Study of Student Consumer of Buddhi Dharma University). In this thesis, the study was conducted on 60 students of Buddhi Dharma University by using questionnaires distributed to students. To measure the presence or absence of influence of product quality and price on consumer buying interest smartphone warranty distributor at PT. Three Agung (Study of Student Consumer Student of Buddhi Dharma University), hence writer conduct research by using multiple linear analysis, correlation coefficient analysis, calculating coefficient of determination and doing hypothesis test by finding F value count then compare F count with F table. From the results of multiple linear regression analysis obtained the equation Y = 14.458 + 0.405 X1 + 0.258 X2 means any change of 1 point then X1 (product quality) has increased or decreased by 0.405, every change of 1 point then X2 (price) has increased or decrease of 0.258. From the analysis of the effect of product quality and price on consumer buying interest, it is known that product quality has a positive and strong correlation to consumer buying interest that is equal to 0.694, the price has a positive and strong correlation to the buying interest of 0.629. Based on hypothesis test results obtained by model 1 of 53.780, model 2 of 31.828, where the value is greater than of 3.16. Thus Ho is rejected and Ha is accepted. This means there is a relationship between product quality and price to consumer buying interest. Keywords: product quality, price and buying interest